Strategies and organizations in transition - Galbraith, Craig (JAI, 2002)
The world of business has always been considered quick and unforgiving, but it is certainly getting even quicker and less forgiving as we enter the new "millennium." New problems have given rise to new approaches while some, but not all, old problems yield new solutions. The theme of this volume "Strategies and organizations in Transition" reflects a world in which variety, change, and unique perspectives are interwoven into the fabric of 21st-century business. The volume articles presented here represent a combination of empirical business research and practical business insight covering a wide range of current and future business issues, with specific emphasis upon the changing dynamics. Articles of particular interest such as Neil Kay's examination of cooperative strategies from a transaction cost theoretical basis, Srinivasan and Brush's examination of modern vertical relationships, and Ryman and Fryxell's analysis of the impact of technology on the health care system are all likely to have implications well beyond the pages of this volume. Equally, "Strategies and Organizations in Transition" also contains Bennett and Stamper's groundbreaking exploration of the complex area of discretionary workplace behaviour and Curt Stiles' exploration of product diversity and specialization in industry. With a more academic focus, Dean and Bamford provide a conceptual examination and interpretation of various economic disequilibrium theories of classical economists as a foundation for extending entrepreneurial research, while Ling, Lubatkin and Schulze explore the relationship between altruism and the governance of family firms. The volume also attempts to further extend the realm of traditional business concerns by its inclusion of two papers that underscore how traditional business and Government constraints impact those wishing to engage in space related entrepreneurial activity.
Keywords: Organizational change.; Strategic planning.; Business planning.; elektronické knihy; electronic books